HUBUNGAN ASUPAN VITAMIN LARUT LEMAK DENGAN KEJADIAN HIPERTENSI PADA PRA LANSIA DI KELURAHAN PELA MAMPANG - Annisa Intanadhia Saroba (2020)
The elderly will undergo physiological changes that can lead to hypertension. However, hypertension does not only occur in the elderly, but also in the pre elderly (45-59 years). Hypertension is one of the major risk factors cause of death worldwide. One factor that can affect hypertension is dietary intake. In foods, there are micronutrients that can prevent hypertension, they are fat soluble vitamins (vitamin A, D, E, and K) and each vitamin has a different role in the prevention of hypertension, such as the role of antioxidants, disabling RAAS, and inhibiting vascular calcification. This study aimed to determine a possible association between fat soluble vitamins intake with the incidence of hypertension among pre elderly in Pela Mampang. This study is an analytical observational study with a cross sectional study design. The sample size was 50 respondents, taken with accidental sampling method. The study was conducted in June 2020. Fat soluble vitamins intake was measured with SQ-FFQ and the incidence of hypertension is known through blood pressure measurement with digital Sphygmomanometer. The statistical test results showed that there is no significant association between the intake of vitamin A (p-value = 1,000), vitamin D (p-value = 1,000), vitamin E (p-value = 1,000), and vitamin K (p-value = 0,495) with the incidence of hypertension among pre elderly in Pela Mampang. Counseling about hypertension and monitoring in the pre-elderly is needed to prevent and treat the incidence of hypertension.